2019
DOI: 10.1186/s42490-019-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing preclinical models of neuroblastoma: driving therapeutic testing

Abstract: Despite advances in cancer therapeutics, particularly in the area of immuno-oncology, successful treatment of neuroblastoma (NB) remains a challenge. NB is the most common cancer in infants under 1 year of age, and accounts for approximately 10% of all pediatric cancers. Currently, children with highrisk NB exhibit a survival rate of 40-50%. The heterogeneous nature of NB makes development of effective therapeutic strategies challenging. Many preclinical models attempt to mimic the tumor phenotype and tumor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 175 publications
0
17
0
Order By: Relevance
“…Syngeneic mouse models are generated by using neuroblastoma cell lines that were originally derived from genetically engineered models to generated allograft mouse models of neuroblastoma ( 209 ). Unlike transgenic mouse models, the mutations are only present in the tumor cells that are used to generate the allograft model, thereby limiting any potential off target effects, these cell lines can be modified to have additional mutations or improve imaging or tracking of tumors, and these mice have a fully functioning immune system, which can better mimic the tumor and tumor microenvironment ( 209 ). However, similar to xenograft models, the cell lines may have genetic alterations as they are grown in vitro , and similar to transgenic models, these cell lines will only carry the specific mutations introduced in the genetically engineered mouse models.…”
Section: Limitations Of In Vivo Preclinical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syngeneic mouse models are generated by using neuroblastoma cell lines that were originally derived from genetically engineered models to generated allograft mouse models of neuroblastoma ( 209 ). Unlike transgenic mouse models, the mutations are only present in the tumor cells that are used to generate the allograft model, thereby limiting any potential off target effects, these cell lines can be modified to have additional mutations or improve imaging or tracking of tumors, and these mice have a fully functioning immune system, which can better mimic the tumor and tumor microenvironment ( 209 ). However, similar to xenograft models, the cell lines may have genetic alterations as they are grown in vitro , and similar to transgenic models, these cell lines will only carry the specific mutations introduced in the genetically engineered mouse models.…”
Section: Limitations Of In Vivo Preclinical Modelsmentioning
confidence: 99%
“…However, similar to xenograft models, the cell lines may have genetic alterations as they are grown in vitro , and similar to transgenic models, these cell lines will only carry the specific mutations introduced in the genetically engineered mouse models. Furthermore, unlike patient xenografts, some of the tumor heterogeneity may not be fully recapitulated ( 199 , 209 ).…”
Section: Limitations Of In Vivo Preclinical Modelsmentioning
confidence: 99%
“…5 ). Additional studies are necessary to elucidate the underlying immunological mechanisms that elicit these protective responses, and these are the focus of several ongoing studies in our group, including in models of high-risk and metastatic neuroblastoma [ 48 , 49 ]. To summarize, we have demonstrated that engineered nanoparticles can serve as an effective platform for priming and/or activating an antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…MCTSs obtained by the aggregation of neuroblastoma cell lines represent an attractive tool to reproduce in vitro the in vivo characteristics of tumor cells with respect to the production of ECM, cell-cell interactions, growth kinetics, cellular heterogeneity, signal pathway activity, and gene expression (13,25). Given the importance of the cell-ECM interaction in a 3D extent, among the most studied behaviors in the neuroblastoma field are the migratory and invasive potentials of cancer cells.…”
Section: Multicellular Tumor Spheroids (Mctss)mentioning
confidence: 99%
“…Still, most of these proposals come from cancers developing in adults, whereas there is a clear deficit of a pre-clinical 3D model providing analysis of drug response in pediatric tumors. This is particularly evident for neuroblastoma, for which a vast majority of scientific questions are still answered by using either 2D studies or the transgenic and xenograft zebrafish and murine models (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%